Development Strategy as a Tourist Attraction in the City of Denpasar Bali Indonesia - Wirawan, Putu Eka; Sudiarta, I Nyoman; Arianty, A.A Ayu Arun Suwi; Tunjungsari, Komang Ratih; Nuruddin (International Journal of Psychosocial Rehabilitation, 2020)
In the world of tourism, attractions become a very decisive entity, attracting tourists to visit. Jongging track is one of the activities that can be done by visitors when traveling. In fact, these activities are now a separate part of tourism as part of Sprot Tourism. This study discusses the potential activities and location of the jongging track in Anggabaya Penatih Village, Denpasar Bali Indonesia City as a tourist attraction. In order to investigate the problems in the field, this study uses a qualitative method with the approach of observation, interviews and study of scientific literature. This study resulted in several findings, one of which was an increase in the economic life of citizens, if the jogging track was professionally managed and developed. Because, these activities can support the development of tourism in the village of Surabaya Surabaya Coach. The benefits of this research, as input for stakeholders and village and regional governments so that they are serious in analyzing all potential tourist destinations in the city of Denpasar, Bali, especially the model of sport tourism, so that it can also contribute directly to people's lives.